2019
DOI: 10.1101/788349
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Defining spatial relationships between spinal cord axons and blood vessels in hydrogel scaffolds

Abstract: 1Spinal cord injury (SCI) results in lifelong paralysis due to the poor regenerative capability of the 2 central nervous system and the hostile microenvironment that is created from processes such as 3 inflammation, scarring, axonal dieback, and demyelination. Hydrogel scaffolds facilitate a 4 permissive regenerative environment and overcome these barriers by reducing scarring. One 5 important other consideration for axonal regeneration is the availability of nutrients and oxygen, 6 making it crucial to furthe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 55 publications
3
5
0
Order By: Relevance
“…Reconnection across complete SCI has been achieved with a nerve autograft and scaffolds 21,22 , particularly when delivering cell types and growth factors [22][23][24][25][26][27][28] . Although the functional outcome in this study was better in rats who received combined therapy, the number of axons through scaffolds was not different between the groups and was in between previously reported with scaffold loaded GDNF secreting Schwann cells 25 or rapamycin with Schwann cells 29 . Rapamycin may reduce the number of regenerating axons, although previous study demonstrated improvement when compared with OPF+ scaffolds loaded with Schwann cells alone 14 .…”
Section: Figure 4 About Heresupporting
confidence: 60%
“…Reconnection across complete SCI has been achieved with a nerve autograft and scaffolds 21,22 , particularly when delivering cell types and growth factors [22][23][24][25][26][27][28] . Although the functional outcome in this study was better in rats who received combined therapy, the number of axons through scaffolds was not different between the groups and was in between previously reported with scaffold loaded GDNF secreting Schwann cells 25 or rapamycin with Schwann cells 29 . Rapamycin may reduce the number of regenerating axons, although previous study demonstrated improvement when compared with OPF+ scaffolds loaded with Schwann cells alone 14 .…”
Section: Figure 4 About Heresupporting
confidence: 60%
“…In addition, finding a proper combination of biomaterials, cell types, and small molecules remain to be elucidated. Our recent findings demonstrated the close relationship between blood vessel formation and the number of regenerating axons (21). We demonstrated that the formation of a capillary structure in turn supported higher numbers of regenerating axons, implicating the importance of vascular normalization in the regenerating spinal cord.…”
Section: Introductionsupporting
confidence: 59%
“…25 mg of PLGA microspheres were added to 250 ul OPF+ liquid polymer thereafter. Scaffold fabrication was as described previously (7) via injection of the liquid polymer with suspended microspheres into a tubular glass mold containing seven parallel aligned wires as placeholders for the channel spaces.…”
Section: Opf+ Scaffold Fabricationmentioning
confidence: 99%
See 2 more Smart Citations